2018
DOI: 10.30770/2572-1852-104.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Egregious Ethical Violations in Medical Practice: Evidence-Informed Recommendations from a Multidisciplinary Working Group

Abstract: This article reports the consensus recommendations of a working group that was convened at the end of a 4-year research project funded by the National Institutes of Health that examined 280 cases of egregious ethical violations in medical practice. The group reviewed data from the parent project, as well as other research on sexual abuse of patients, criminal prescribing of controlled substances, and unnecessary invasive procedures that were prosecuted as fraud. The working group embraced the goals of making s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…One benefit of using Behavior substitution is that this strategy may be more acceptable to healthcare professionals (HCPs) than current ways to reduce low-value or harmful care, which may be more punitive and extreme (e.g. financial penalties, medical practice sanctions, or restrictive measures) 7 …”
Section: A Technique For De-implementing Low-value Carementioning
confidence: 99%
“…One benefit of using Behavior substitution is that this strategy may be more acceptable to healthcare professionals (HCPs) than current ways to reduce low-value or harmful care, which may be more punitive and extreme (e.g. financial penalties, medical practice sanctions, or restrictive measures) 7 …”
Section: A Technique For De-implementing Low-value Carementioning
confidence: 99%
“…[30,31] This is probably the consequence of their embarrassing and sensitive nature, so that only direct participants are truly privy to them. [17][18][19][20]…”
Section: Research Subjects Protectionsmentioning
confidence: 99%
“…[3,[13][14][15][16] Probably there is no more egregious ethical breach of scientific integrity in medical research than deviations or violations (i.e., non-compliance) of Human Research Subjects Protections, especially anything abrogating adequate informed consent to participate in research (e.g., no consent obtained, wrong consent, language not translated, improperly completed consent, consent P&P not followed, consent undocumented, etc.). [17][18][19]20] The integrity of Human Research Subjects Protections is commonly considered inviolable and sacrosanct. [20] Unfortunately, violations are fairly common, even though there are a plethora of formally established safeguards, policies, procedures, regulations and agencies and agents, as well as punitive sanctions for such violations.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of over 200 state and federal drug enforcement cases brought against healthcare providers between 2009 and 2014 found that at least 15% involved “practitioners stealing drugs for personal use.” 20 Similarly, a review of 100 state licensing board cases of egregious ethical violations occurring in 28 states between 2008 and 2013 found that 17% were motivated by the doctors' own substance use disorders 21 . Of these cases, 93% involved opioid prescriptions.…”
Section: A Critical Ethical Dividementioning
confidence: 99%